When Mahāyāna Meets Theravāda: The Position of Chinese Bhikṣuṇīs in Contemporary Myanmar - Chiu, Tzu-Lung (Religions, 2022)
Mahāyāna and Theravāda are the two major traditions of Buddhism in contemporary Asia. Although they share many similar teachings, there are long-standing disputes between their respective sets of adherents, touching on doctrine, ritual, religious practices, and the ultimate goal, among other matters. Drawing on fieldwork conducted in Yangon and Mandalay, this study explores gender’s role in the position of Sino-Burmese Mahāyāna bhikṣuṇīs in the sociocultural context of Theravāda-majority Myanmar, where the full bhikṣuṇī lineage of Theravāda Buddhism has died out. Its findings, firstly, shed light on how the local Theravāda ethos inevitably affects Sino-Burmese Mahāyāna nuns’ positions and experiences of religious- and ethnic-minority status. Secondly, they demonstrate the gender dynamics of Sino-Burmese nuns’ interactions both with indigenous Burmese monks and Myanmar’s ethnic-Chinese laity. As such, this research opens up a fresh perspective on these nuns’ monastic lives, to which scant scholarly attention has hitherto been paid. Specifically, it argues that while Sino-Burmese nuns are subjected to “double suffering” on both gender and ethnoreligious minority grounds, they play an important role in shaping the future of Chinese Mahāyāna Buddhism by educating the next generation of monastics and serving the religious needs of the wider Sino-Burmese community in Myanmar.